Serum folate, vitamin B-12 and cognitive function in middle and older age: The HAPIEE study - Horvat, Pia; Gardiner, Julian; Kubinova, Ruzena; Pajak, Andrzej; Tamosiunas, Abdonas; Schöttker, Ben; Pikhart, Hynek; Peasey, Anne; Jansen, Eugene; Bobak, Martin (Experimental gerontology, 2016)
BACKGROUND: Nutrient status of B vitamins, particularly folate and vitamin B-12, may be related to cognitive ageing but epidemiological evidence remains inconclusive. OBJECTIVE: The aim of this study was to estimate the association of serum folate and vitamin B-12 concentrations with cognitive function in middle-aged and older adults from three Central and Eastern European populations. METHODS: Men and women aged 45-69 at baseline participating in the Health, Alcohol and Psychosocial factors in Eastern Europe (HAPIEE) study were recruited in Krakow (Poland), Kaunas (Lithuania) and six urban centres in the Czech Republic. Tests of immediate and delayed recall, verbal fluency and letter search were administered at baseline and repeated in 2006-2008. Serum concentrations of biomarkers at baseline were measured in a sub-sample of participants. Associations of vitamin quartiles with baseline (n=4166) and follow-up (n=2739) cognitive domain-specific z-scores were estimated using multiple linear regression. RESULTS: After adjusting for confounders, folate was positively associated with letter search and vitamin B-12 with word recall in cross-sectional analyses. In prospective analyses, participants in the highest quartile of folate had higher verbal fluency (p<0.01) and immediate recall (p<0.05) scores compared to those in the bottom quartile. In addition, participants in the highest quartile of vitamin B-12 had significantly higher verbal fluency scores (β=0.12; 95% CI=0.02, 0.21). CONCLUSIONS: Folate and vitamin B-12 were positively associated with performance in some but not all cognitive domains in older Central and Eastern Europeans. These findings do not lend unequivocal support to potential importance of folate and vitamin B-12 status for cognitive function in older age. Long-term longitudinal studies and randomised trials are required before drawing conclusions on the role of these vitamins in cognitive decline.
Keywords: Memory, Short-Term; krátkodobá paměť; Nutrition Assessment; Europe; Female; verbální chování; biologické markery; Age Factors; Neuropsychological Tests; Biomarkers; Vitamin B-12; Folate; Geriatric Assessment; ženské pohlaví; Linear Models; průřezové studie; Aging; Folic Acid; věkové faktory; neuropsychologické testy; lidé; Nutritional Status; Evropa; geriatrické hodnocení; lineární modely; nutriční stav; kognice; prospektivní studie; Cross-Sectional Studies; Male; Aged; Prospective Studies; stárnutí; Vitamin B 12; Ageing; Eastern Europe; Cognition; Cognitive function; lidé středního věku; hodnocení stavu výživy; senioři; mužské pohlaví; vitamin B 12; Middle Aged; kyselina listová; Verbal Behavior; Humans